The economic effects of direct democracy: a first global assessment - Lorenz Blume; Jens Müller; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2007)
This is the first study that assesses the economic effects of direct democratic institutions on a cross country basis. Its results are based on up to six new measures produced to reflect the legislative basis for using direct democratic institutions as well as their factual use. In addition, a more general overall indicator is used. On the basis of these two different data sets only some of the results of the former intra-country studies are confirmed. An analysis based on the more general democracy index for 87 countries shows that a higher degree of direct democracy leads to lower budget deficits and higher government effectiveness. The effects on government expenditure, corruption and productivity have the expected signs but do not reach conventional levels of significance. A more fine grained analysis for a cross section of 88 countries based on the second data set shows that institutional detail matters a great deal. In particular, the mere possibility of drawing on direct-democratic institutions is often not sufficient to induce significant effects whereas the frequency of their factual use has a number of substantive effects on economic variables.
Keywords: H1; H3; H5; H8; 330; direct democracy; economic effects of constitutions; positive constitutional economics; Demokratie; Makroökonomischer Einfluss; Ökonomische Theorie der Demokratie; Schätzung; Welt